2021
DOI: 10.21203/rs.3.rs-900915/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The quality of life among Sudanese Patients with Epilepsy, Khartoum, Sudan

Abstract: Introduction:This is the first study done in the national center for neurological sciences, Khartoum state to assess the quality of life above hundred Sudanese epileptic patients, in the period from September to December 2020.Methodology: This is a descriptive cross sectional study, data was collected using interviewing questionnaire and this questionnaire was modified from SF-36 model.Results: Most of the patients are from the urban area (60.2%), housewives are most of them, most of the patients were single a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(42 reference statements)
0
1
1
Order By: Relevance
“…On the other hand, this study disagreed with other previous studies, which showed that the PT value was discovered to be significantly lesser in hypothyroid & hyperthyroid cases when compared with the control group [9,15].…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, this study disagreed with other previous studies, which showed that the PT value was discovered to be significantly lesser in hypothyroid & hyperthyroid cases when compared with the control group [9,15].…”
Section: Discussioncontrasting
confidence: 99%
“…MAP in humans in the Sudan has never been investigated, neither in diseases that have been linked to it earlier (CD or IBD) nor in other diseases, more likely due to the scarce information on these diseases [ 32 – 34 ]. However, because of the relatively high prevalence of MAP in cattle in Khartoum, Sudan [ 35 ] in addition to the close contact between humans and animals, we hypothesize that MAP prevalence in human is higher than expected.…”
Section: Introductionmentioning
confidence: 99%